THE ROLE OF HALAL CERTIFICATION IN ENHANCING THE ADDED VALUE OF LOCAL FOOD: A CASE STUDY OF CABUK WIJEN FROM WONOGIRI, INDONESIA - Rusdan, Ilzamha Hadijah; Najwa, Aida Fajrin (Ar Rehla: Journal of Islamic Tourism Halal Food Islamic Traveling and Creative Economy, 2025)
Abstract: This study examines the role of halal certification in enhancing the added value of local food products, with a particular focus on cabuk wijen, a traditional dish from Wonogiri, Central Java. As global demand for halal food continues to grow, cabuk wijen—a fermented product made from sesame oil cake using traditional processing methods—represents a promising candidate for entry into international halal markets. Halal certification not only ensures compliance with Islamic dietary law but also strengthens consumer confidence, among both Muslim and non-Muslim consumers, by underscoring food safety and ethical production practices. The study employs a narrative literature review that analyzes journal articles, books, and policy documents relevant to halal certification, local food, and the development of small and medium-sized enterprises (SMEs). These sources were purposively selected based on their thematic relevance and contribution to understanding value enhancement. The analysis indicates that halal certification increases the added value of cabuk wijen through several key mechanisms: reinforcing perceptions of safety and quality, expanding market access, shaping a halal-oriented brand image, and improving competitiveness relative to similar products. The findings also identify challenges such as certification costs, procedural complexity, and variations in halal standards across countries, which pose substantial barriers for SMEs. Addressing these challenges has the potential to strengthen global competitiveness, advance theoretical insights into the relationship between halal certification and the added value of local food products, and support the preservation of traditional culinary heritage such as cabuk wijen. Keywords: halal certification; local food; cabuk wijen; traditional food Abstrak: Penelitian ini mengeksplorasi peran sertifikasi halal dalam meningkatkan nilai produk pangan lokal, dengan fokus pada cabuk wijen, sebuah hidangan tradisional dari Wonogiri, Jawa Tengah. Seiring meningkatnya permintaan global terhadap makanan halal, cabuk wijen—produk fermentasi yang dibuat dari ampas minyak wijen dan metode pengolahan tradisional—memiliki potensi besar untuk memasuki pasar halal internasional. Sertifikasi halal tidak hanya memastikan kepatuhan terhadap hukum diet Islam tetapi juga meningkatkan kepercayaan konsumen, baik dari kalangan Muslim maupun non-Muslim, dengan menekankan pada aspek keamanan pangan dan praktik produksi yang etis. Penelitian ini merupakan tinjauan literatur naratif yang menganalisis berbagai artikel jurnal, buku, dan dokumen kebijakan yang relevan dengan sertifikasi halal, pangan lokal, dan pengembangan usaha kecil dan menengah (UKM), yang dipilih secara purposif berdasarkan kesesuaian topik dan kontribusi terhadap penguatan nilai tambah. Analisis menunjukkan bahwa sertifikasi halal meningkatkan nilai tambah cabuk wijen melalui beberapa mekanisme utama: penguatan persepsi keamanan dan kualitas, perluasan akses pasar, pembentukan citra merek halal, serta peningkatan daya saing terhadap produk sejenis. Temuan juga mengidentifikasi tantangan berupa biaya sertifikasi, kompleksitas prosedur, dan perbedaan standar halal antar negara yang menjadi hambatan bagi UKM. Mengatasi hambatan ini berpotensi memberikan kontribusi signifikan terhadap penguatan daya saing global, pengembangan teori mengenai hubungan antara sertifikasi halal dan nilai tambah pangan lokal, serta pelestarian budaya kuliner tradisional seperti cabuk wijen. Kata Kunci: sertifikasi halal; makanan lokal; cabuk wijen; makanan tradisional